The Relations of Economic-Political Power to the Development of Digital Economy in Asia - Halifa Haqqi; Andika Drajat Murdani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The relationship between the two is intricate, and this includes how it affects the development of the digital economy. The expansion of the digital economy is performing well throughout Asia. However, very few people have examined it from the viewpoint of political economy. This study focuses on examining the political-economic interactions that take place as Asia's digital economy grows. With library research, the research method takes a descriptive qualitative approach. Political economy analysis was used to conduct the analysis, and it was found that while other Asian nations lack political strength, some of them can to create ecosystems and maintain control of their national digital economies. Therefore, depending on the current political and economic forces, there are differences in several of nations.